Information security and privacy : 12th Australasian Conference, ACISP 2007 Townsville, Australia, July 2-4, 2007 : proceedings - ACISP; Pieprzyk, Josef; Ghodosi, Hossein; Dawson, Ed (Edward) (Lecture Notes in Computer Science, 2007)
Here is a highly relevant book that covers a wide array of key aspects in information security. It constitutes the refereed proceedings of the 12th Australasian Conference on Information Security and Privacy held in Townsville, Australia in July 2007. The 33 revised full papers presented were carefully reviewed and selected from 132 submissions. The papers are organized in topical sections on stream ciphers, hashing, biometrics, secret sharing, cryptanalysis, public key cryptography, authentication, e-commerce, and security.